1997
DOI: 10.1016/s0092-8674(00)81877-2
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the Ca2+ Channel β Subunit Gene Cchb4 Is Associated with Ataxia and Seizures in the Lethargic (lh) Mouse

Abstract: Ca2+ channel beta subunits regulate voltage-dependent calcium currents through direct interaction with alpha 1 subunits. The beta- and alpha 1-binding motifs are conserved, and all beta subunits can stimulate current amplitude, voltage dependence, and kinetics when coexpressed with various alpha 1 subunits. We used a positional candidate approach to determine that the ataxia and seizures in the lethargic (lh) mouse arise from mutation of the beta-subunit gene Cchb4 on mouse chromosome 2. A four-nucleotide inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
229
3
2

Year Published

1998
1998
2004
2004

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 392 publications
(243 citation statements)
references
References 48 publications
9
229
3
2
Order By: Relevance
“…A significant reduction in calcium current density was recorded from Purkinje cells of tottering mice (28). A splice site mutation in the β4 subunit gene Cacnb4 that produces a truncated, nonfunctional protein was identified in the mouse mutant lethargic (12). lethargic mice exhibit absence seizures, lethargy, and ataxia, and go through a crisis during the third week of life.…”
Section: Voltage-gated Calcium Channelsmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant reduction in calcium current density was recorded from Purkinje cells of tottering mice (28). A splice site mutation in the β4 subunit gene Cacnb4 that produces a truncated, nonfunctional protein was identified in the mouse mutant lethargic (12). lethargic mice exhibit absence seizures, lethargy, and ataxia, and go through a crisis during the third week of life.…”
Section: Voltage-gated Calcium Channelsmentioning
confidence: 99%
“…Underrepresentation of one allele could be caused by a mutation in regulatory sequences or reduced mRNA stability due to a transcribed variant. The mouse calcium channel mutations lethargic (12) and spike wave epilepsy (22) both reduce mRNA stability in addition to changing the protein sequence.…”
Section: Future Prospects Additional Monogenic Epilepsy Genes In Humanmentioning
confidence: 99%
“…Interestingly, it was recently shown that a mutation in the calcium channel 4 subunit gene is associated with ataxia and seizures in the lethargic mouse (1h). 102 Homozygotes of the 1h mouse are characterised by ataxia, lethargic behaviour, motor seizures and seizures resembling absence seizures of human petit mal epilepsy. 102…”
Section: P/q Type Calcium Channel α 1a Subunit Gene In Mice With Epilmentioning
confidence: 99%
“…Knockout of ␤ 3 reduces the activities of neuronal L-type and N-type channels (20). The lethargic mouse, an effective ␤ 4 null mutant, is characterized by seizure activity and ataxia; however, the density of presynaptic calcium channels is not affected possibly because of compensation from other ␤ subunit subtypes (19,44). Indeed, the combinatorial complexity of multiple ␤ and ␣ 1 subunits has prevented detailed insights into the precise function of ␤ subunits in synaptic terminals in vivo (21).…”
Section: Lymnaea Neurons Express a Ca V ␤ Subunit-a Full-lengthmentioning
confidence: 99%